2022
DOI: 10.3390/make4040042
|View full text |Cite
|
Sign up to set email alerts
|

On the Application of Artificial Neural Network for Classification of Incipient Faults in Dissolved Gas Analysis of Power Transformers

Abstract: Oil-submerged transformer is one of the inherent instruments in the South African power system. Transformer malfunction or impairment may interpose the operation of the electric power distribution and transmission system, coupled with liability for high overhaul costs. Hence, recognition of inchoate faults in an oil-submerged transformer is indispensable and it has turned into an intriguing subject of interest by utility owners and transformer manufacturers. This work proposes a hybrid implementation of a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The dataset is composed of 815 samples used for training and validation phases obtained from reference [19][20][21][22][23][24][25]. The data is distributed as 691 normal operation samples, 52 thermal fault samples, and 72 electrical fault samples for five types of combustible gases (H 2 , CH 4 , C 2 H 2 , C 2 H 4 , and C 2 H 6 ).…”
Section: Cause Of Gas Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset is composed of 815 samples used for training and validation phases obtained from reference [19][20][21][22][23][24][25]. The data is distributed as 691 normal operation samples, 52 thermal fault samples, and 72 electrical fault samples for five types of combustible gases (H 2 , CH 4 , C 2 H 2 , C 2 H 4 , and C 2 H 6 ).…”
Section: Cause Of Gas Generationmentioning
confidence: 99%
“…Topics related to the application of artificial neural networks (ANNs) in the analysis of the operating conditions of power transformers and electrical energy systems have currently received attention [13][14][15]. In recent years, a series of studies and research have been published in this field, demonstrating the growing interest and relevance of these approaches [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…During training, the main parameters of the network model are progressively adjusted until a mapping is established between the information on the dissolved gas ratios and the actual fault present [40]. In [41,42], an ANN trained using the Levenberg-Marquardt algorithm was developed to classify seven transformer incipient fault types. Three combustible gas ratios were calculated and the IEC ratio method was deployed in interpreting the fault present.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…In addition, the operating conditions of chiller units are varied, and certain operating parameters are highly similar in the micro-fault state and the no-fault state in incipient faults [5]. Due to the complexity and uncertainty of the system, machine learning algorithms like Artificial Neural Networks (ANNs) [6] and support vector machines (SVMs) [7] were applied to the diagnosis of minor faults, and some results have been achieved. In the study of chiller fault diagnosis, study [8] used an ANN to diagnose various faults in chillers and found that the diagnosis of system faults is more difficult than local faults.…”
Section: Introductionmentioning
confidence: 99%